Reflexive Wrting in Inclusive Teacher Education (Pedagogical Horizons, 2019)
In teacher education inclusion is a mean topic of higher education didactics. One problem is that trainee teacher students often don't have practical experiences. Reflexive Writing is an approach that could unlock this difficult field. Two examples are given in this text that show how trainee teacher students can be animated to engage in this topic. The theoretical background is descriped (inclusive teacher education, reflexive writing) as well as two trainee teacher students' works. The argumentation patterns are carved out and integrated in the didactical context.
Keywords: Reflexive writing; inclusive teacher education; Higher Education